TEKNIK DAN METODE PENERJEMAHAN NONOSHIRI KOTOBA (KATA UMPATAN) PADA MANGA BEELZEBUB KARYA RYUHEI TAMURA - Suherman, Wike (Humanis; Volume 14. No.2. Pebruari 2016)
This thesis entitled “Translation Technique and Method of Nonoshiri Kotoba (Swearwords) of Beelzebub Manga by Ryuhei Tamura”. The purpose of this study is to know the translation technique and method of swearwords that applied in Beelzebub Manga vol. 1–5. This research used translation technique by Molina and Albir (2002) and translation method by Newmark (1998) as the theories. The data of this research were analyzed using Translational Equivalent method and supported with Immediate Constituent Analysis. The data were analyzed in two steps, the first step was analyzing the translation technique in swearwords of Beelzebub manga and the second step was analyzing translation method of swearwords of Beelzebub manga. The result shows that from 162 data, there are four technique applied, namely 143 data (81,48%) of literal translation, 18 data (11,11%) of reduction, 8 data (4,94%) of discursive creation, and 2 data (1,24%) of amplification. The translation method is source language oriented method.
Keywords: nonoshiri kotoba (swearwords), translation technique, translation method